Sacred Places and Symbolic Altars in Medellin Lugares sagrados e altares simbólicos em Medellín [Lugares sagrados y altares simbólicos en Medellín] (2019)
We make an invitation to visit places where intercultural processes are evident and borders of past and present, rural and urban, as well as the sacred and profane blur. Recognizing the aesthetic singularity that inhabits Medellin city, we were able to relate heteroclite objects in what is recognizable as contemporary rituals and, in this sense, the aesthetics referred to as Chicanas with the intimate scenes of meaning in Medellin, which reflect in visual cartographies of beliefs that evoke Christian religious icons intimately connected with Antioquia s peasant culture. We present a series of photographs to establish connections at the level of the symbolic structures between the Bello Oriente neighborhood altars and some Chicano art manifestations characterized by the use of religious, political, and cultural symbols that reflect social and identity problems in urban scenarios. © 2019 Universidad del Rosario. All Rights Reserved.